SALAS CARREÑO, Guillermo. Social dynamic and mining. Puna pastoral families and the presence of the Antamina project (1997-2002). Lima: IEP, 2008. 409 pp. - Málaga Sabogal, Ximena (2010)
The review does not present a summary.